2016
DOI: 10.11648/j.ijbecs.20160201.11
|View full text |Cite
|
Sign up to set email alerts
|

Unusual HBV Mixed Genotype Infections Among Hepatitis Type B Iraqi Patients in Wasit Province/Iraq

Abstract: Hepatitis B virus (HBV) is the leading cause to liver disease, cirrhosis and primary liver cancer. About 1 million people die from HBV each year, which equates to about 2 HBV related deaths each minute. Depending on the virus sequence homogeneity as a minimum 10 genotypes (A to J) and numerous subgenotypes have been identified. Hepatitis B virus variants may be differ in their virulence, models of serologic reactivity, pathogenicity, response to treatment and global distribution. This study was carried out to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 33 publications
0
0
1
Order By: Relevance
“…In Baghdad, one study reported that genotype D contributes to 80% of the infection, which is the most prevalent in CHB patients, and mixed genotypes F and D contribute to 20% of the infection (16) . These findings disagreed with Ali et al (17) in Wasit (Iraq) who reported that there was no single HBV genotype infection and that 77.7% of their patients had mixed infection with five genotypes out of six. Also, another study in Baghdad that involved eighty CHB patients reported six HBV genotypes (A, B, C, D, E, F).…”
Section: Discussioncontrasting
confidence: 81%
“…In Baghdad, one study reported that genotype D contributes to 80% of the infection, which is the most prevalent in CHB patients, and mixed genotypes F and D contribute to 20% of the infection (16) . These findings disagreed with Ali et al (17) in Wasit (Iraq) who reported that there was no single HBV genotype infection and that 77.7% of their patients had mixed infection with five genotypes out of six. Also, another study in Baghdad that involved eighty CHB patients reported six HBV genotypes (A, B, C, D, E, F).…”
Section: Discussioncontrasting
confidence: 81%